AN AYURVEDIC PERSPECTIVE TO GERIATRIC EYE DISORDERS WITH SPECIAL REFERENCE TO AGE RELATED MACULAR DEGENERATION (A.M.D.) (International Journal of Ayurveda and Pharma Research, 2016)
Recent advancements have remarkably increased average lifespan in human beings. It is obvious and inevitable that various changes occur in ocular tissue as age progresses. However, changed lifestyle has resulted in early ageing. Geriatric eye disorders are going to be a big challenge in the next years. Cataract, Glaucoma, dry eye syndrome, age related macular degeneration are the main disorders occurring in old age and can grossly affect visual acuity.Age related macular degeneration (A.M.D.) is a painless degenerative condition of photoreceptor cells in the macular area of the retina; having two types dry and wet AMD. A.M.D. is one of the leading causes of irreversible blindness above age of 50. There are nearly 23.5 million people suffering from this disease in the world.There is no satisfactory treatment for this disease in modern medicine. Therefore, attempt has been made to find out better solution through Ayurveda. Our aim should be to prevent and treat the diseases in early stage so that we can preserve our eyesight even in the old age. Hence Rasayana chikitsa (rejuvenation) will be helpful in prolonging degenerative changes. In this conceptual study, various changes occurring in eye due to ageing are studied. In A.M.D., symptoms are similar to Timira (Patalgata dosha dushti).So according to Dosha, Dushya vitiation; basic line of treatment is suggested. As A.M.D. and other geriatric eye conditions are multi factorial, holistic approach with combined therapy with Chakshushya Rasayanas, eye exercises & yoga will be more beneficial than a single drug therapy.